Comparison of Cranium Shape in Hamdani and Awassi Sheep using Dorsal and Lateral Landmarks - Demircioglu, Ismail; Demiraslan, Yasin; Guzel, Baris Can; Kocyigit, Ali; Demircioglu, Aysegul (Zoological Soc Pakistan, 2024)
The aim of this study is to determine whether or not kinship relations, and breed factors of Hamdani and Awassi sheep have an effect on the shape by using geometric morphometry method through their crania. For this purpose, heads of 7 adult Hamdani sheep and 10 adult Awassi sheep were used for the dorsal analysis of cranium and heads of 8 adult Hamdani and 9 adult Awassi sheep were used for lateral analysis of cranium. In the dorsal and lateral comparison of the breeds, the first principal component (PC1) explained 41.905% and 39.078% of the total shape difference, respectively. When the procrustes coordinates were examined, it was found that the samples were both dorsally and laterally mostly similar to the samples in their own group. Consequently, it is thought that the shape analysis of the crania of Hamdani and Awassi sheep breeds was made in detail by geometric morphometry method; thus, yielding the results that may be basic data for many disciplines, especially zooarchaeology, taxonomy, and forensic sciences were presented.
Keywords: Awassi; Geometric morphometry; Hamdani; Sheep; Procrustes coordinates